Impact of digitalization on the labor market - Karmys, G.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article a documentary analysis of scientific data was conducted to refute the hypothesis about the effect of automation on general unemployment. Key factors influencing the labor market, such as demography, competitiveness, globalization and digitalization, are identified and disclosed. In this paper no assessment was mad from the above factors that has the greatest impact on the labor market, and attention is focused on the «digitalization» factor and its effect on the demand for jobs. There are 6 main criteria for digitalization: prevalence, availability, reliability, usability and skill. The serious impact of digitalization on the labor market in the early stages of development since the 2000s was illustrated. At an early stage of development, digitization already had a serious impact on the labor market. The increase in demand for specialties not only in the information and communication field, but also in other non-technology-related industries, that involve close contact with people, which can not be adequately automated was marked. The conclusion is made about the further influence of digitalization on the labor market; the task is a set to further study of the impact of digitalization on the creation and loss of jobs.